Enraizamento de estacas de figueira “Roxo-de-Valinhos” imersas em concentrações de extrato aquoso de tiririca (Cyperus rotundus) - Alves, Anderson Araujo (Universidade Federal Rural do Semi-Árido, 2019)
The commercial propagation in the fig tree is carried out via cuttings, but due to the high temperatures and low relative humidity of the air, found in the semi-arid region, the cuttings undergo strong dehydration, harming the rooting and sprouting of the same ones, being necessary to accelerate the rooting process and one way to promote better rooting and sprouting of cuttings is the use of synthetic and natural phytohormones, one of the plants that stands out for the high level of natural rooting hormone is tiririca. The objective of this work was to evaluate the use of aqueous extract of tiririca on the rooting capacity of the fig tree "Roxo de Valinhos". The experiment was conducted in a greenhouse belonging to the Universidade Federal Rural do Semi-árido (UFERSA), in Mossoró-RN. The experimental design was completely randomized. The treatments consisted of five concentrations of aqueous extract of tiririca (0%, 25%, 50%, 75% and 100%), with ten replicates per treatment. The following characteristics were analyzed at 38 days after planting: Sprouting length, number of sprouts, diameter of sprouts, number of leaves, percentage of sprouts sprouted, percentage of rooted cuttings, percentage of live cuttings, length of largest root, number of roots per stem and mean root volume. It was concluded that the use of aqueous extract of tiririca positively influenced root length, diameter of shoots, percentage of live cuttings and root volume, evidencing the hormonal potential of tiririca, being the stakes immersion time limiting factor for better results in the studied variables.
Monografia
Keywords: Ficus carica L; Produção de mudas; Hormônio natural; Propagação; Ficus carica L; Seedling production; Natural hormone; Propagation; CIENCIAS AGRARIAS::AGRONOMIA